POEMS syndrome: A rare entity - Chaganti P. Devi; Basimalla R. Stephenson; P. Ramana Kumari; Panchakarla G. Vani; Swargam P. Madhooli (Indian Journal of Pathology and Microbiology)
POEMS syndrome is a rare paraneoplastic syndrome due to an underlying plasma cell disorder. The diagnosis of POEMS syndrome can be a challenge. A good history, physical examination, and appropriate testing can aid in establishing its diagnosis. We are presenting the case of a 75-year-old man who was diagnosed with POEMS syndrome.